Pengaruh Pembiasaan Menghafal Juz ‘Amma Terhadap Peningkatan Aspek Afektif Siswa Pada Program Tahfidz Fase C Di SDIT Miftahul Ulum Cisurupan Garut - Fauziah, Hapsah; Rohali, Syifa (STAI Al-Musaddadiyah Garut, 2025)
The Qur'an is the main obligation for every Muslim and should also be started early so that the child's mind is still clean and his memory is still strong. One form of learning the Qur'an that can be started early is Tahfidzul Qur'an. This can be realized when educational institutions such as schools have religious activities, one of which is about habituating the Juz 'Amma memorization program to students. This study uses a descriptive quantitative method because in this study the results are presented in the form of statistical figures. This quantitative research is carried out to clarify something based on data obtained from the field. The results of the study showed that the habit of memorizing Juz 'Amma in the tahfidz program had an average of 4,53 thus the average was in the interval area of 4,01-5,00 included in the category of